Lipids of Branhamella catarrhalis and Neisseria gonorrhoeae. - Beebe, J L (1976)
Three strains of Branhamella catarrhalis and three strains of Neisseria gonorrhoeae were analyzed with regard to their phospholipid and neutral lipid composition. B. catarrhalis (ATCC 23246) contained 5.12 +/- 0.34% lipid, determined gravimetrically, compared to 8.56 +/- 0.15% and 9.73 +/- 0.06% for two strains of N. gonorrhoeae. Cardiolipin, phosphatidylglycerol, and phosphatidyl-ethanolamine were identified in extracts of both species. In addition, B. catarrhalis contained small amounts of phosphatidylcholine, and N. gonorrhoeae contained small amounts of lyso-phosphatidylethanolamine, which accumulated with autolysis accompanying late cell culture growth. The kinetics of change of relative amounts of phospholipids in both species were measured and found to differ substantially. Neutral lipid accounted for 30.4% of the total lipid of B. catarrhalis (ATCC 23246) and 7.6% of the total lipid of N. gonorrhoeae NYH 002. Hydrocarbons, triglycerides, free fatty acids, coenzyme Q, diglycerides, and free hydroxy fatty acids were identified in the neutral lipid fraction of both species. The three strains of N. gonorrhoeae, sensitive, intermediate, and resistant to penicillin, exhibited no significant difference in the composition or metabolism of phospholipid.